2017
DOI: 10.1111/fima.12166
|View full text |Cite
|
Sign up to set email alerts
|

CEO Age, Risk Incentives, and Hedging Strategy

Abstract: We test whether managerial preferences explain how firms hedge, using hand‐collected data on derivative portfolios in the oil and gas industry. How firms hedge involves choosing between linear contracts and put options, and deciding whether to finance these hedging positions with cash on hand or by selling call options. The likelihood of being a hedger increases with chief executive officer (CEO) age, and near‐retirement CEOs prefer linear hedging instruments. The predictions of the managerial risk incentives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 65 publications
5
45
0
Order By: Relevance
“…We measure managerial risk incentive by their options vega (Chava and Purnanandam, ; Croci, Del Giudice, and Jankensgard, ), with the options valued using the Black‐Scholes () model . Tests are based on a sample of 26,579 Form 10‐K filings (firm‐year observations) covering 1993‐2015.…”
mentioning
confidence: 99%
“…We measure managerial risk incentive by their options vega (Chava and Purnanandam, ; Croci, Del Giudice, and Jankensgard, ), with the options valued using the Black‐Scholes () model . Tests are based on a sample of 26,579 Form 10‐K filings (firm‐year observations) covering 1993‐2015.…”
mentioning
confidence: 99%
“…Yim () shows that younger CEOs are more likely to conduct acquisitions. Croci et al () find the propensity of using hedging strategies to reduce portfolio risk increases with CEO age. Axelson and Bond () suggest that adverse selection is more severe for younger CEOs, which incentivizes them to take more aggressive policies to avoid being labeled as “Low ability.” Bamber, Jiang, and Wang () show that certain disclosure style is more conservative for old managers.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…There is indeed substantial richness in terms of how firms hedge (Adam 2009;Croci et al 2017). Three main strategies are discernable in the oil and gas industry: a cash-financed insurance strategy 7 , a linear strategy 8 , and the collar strategy (Jin and Jorion 2006;Croci et al 2017). 9 Another way a derivative portfolio can be characterized is in terms of its maturity, i.e., how far out in time its positions are due.…”
Section: Selective Hedgingmentioning
confidence: 99%
“…Inside ownership furthermore increases the likelihood of a change in the dominant hedging style. Previous studies have shown that there is substantial variation in hedging style, which refers to the specific combination of different types of derivative instruments used (Adam 2009;Croci et al 2017). A high rate of change in hedging style (e.g., switching from using mainly forward contracts to options) is suggestive of selective hedging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation